Character design for the Tapel Saga mobile game inspired by Malangan masks and Urban Legends - Arif, Novida Nur Miftakhul (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
Character design is a crucial aspect of video games, requiring a solid understanding of design principles and an appreciation of the sources of inspiration, mainly when aiming to promote traditional culture, such as the Malangan masks. "Tapel Saga" attempts to interpret the esoteric aspects of Malangan masks and urban legends into a mobile game format. The representation of traditional cultural values can be visualised in character design by adhering to character design principles and considering the tastes of the target audience, namely the younger generation. The literature review on Malangan masks and Malang urban legends is limited; therefore, most data on Malangan masks was obtained through observation and interviews with practitioners and enthusiasts in the Malang region, specifically Jabung. Characters in the mobile game were created using character design methods that consider design principles such as the utilisation of basic shapes, target audience characteristics, and sources of inspiration from traditional culture. The development of the Tapel Saga mobile game character design serves as an actualisation of conventional culture, providing a reference for visual creativity and expanding ideas for the growth of Indonesia's video game industry, which is currently experiencing significant growth.